Tumbuhan Echinodorus Radicans Dan Sagittaria Lancifolia Sebagai Fitoremediator Detergen Dan Logam Berat - Rony Irawanto (Al-Ard: Jurnal Teknik Lingkungan, 2019)
Indonesia is a tropical country that wellknow as mega-biodiversity, but a small diversity is known and utilized. The predicate as mega biodiversity country, now augmented with predicate as hot spot country, a term that high levels of forest destruction and loss biodiversity. Others high development efforts that ignore of environmental aspects, improving the quality and quantity of various types of pollutants, which directly or indirectly will affect the environment. Water pollutants came from, agricultural and industrial wastewater domestic that polluted rivers. While the condition of waste water is still directly discharged into the drainage channel that will lead to water bodies without processing. The concept of using plants as natural technologies framework to solve environmental problems are known as phytotechnology. One of phytotechnology application is phytoremediation. Phytoremediation is used of plants process in restoring environmental quality from pollutants that contaminate environmental. Given the potential of aquatic plants as phytoremediators, the effort to conserve the aquatic plants diversity in Purwodadi Botanic Garden (PBG) is very important. Therefore, research related to phytoremediation using aquatic plants needs to be done. This study aims to determine the ability of aquatic plants Echinodorus radicans and Sagittaria lancifolia in phytoremediation of organic wastewaste (detergent) and inorganic wastewaste (heavy metals). This research is descriptive with observation and experimental, based on literature study, observation on aquatic plants collection and green house experiment at PBG, and laboratory analysis in Universitas of Brawijaya. Aquatic plants from PBG are Echinodorus radicans and Sagittaria lancifolia based on previous studies are known to have potential in wastewater treatment, not only form river quality but also used in household treatment, leachate, water treatment plant installation, industrial leather waste, slaughterhouses, tofu industry, even hospital wastewater. While the test results of heavy metal content such as Cd, Cr, Cu, Hg and Pb is known to exist and accumulated in plant leaf tissue in fields. Also evidenced by results of morphological and experimental observations in PBG greenhouses using both species, has demonstrated its ability in phytoremediation against organic contaminants and heavy metal. Keywords: Phytoremediation, Echinodorus radicans, Sagittaria lancifolia, Wastewater.